The Complete 101 Collection - Maxwell, John C., 1947- (Nashville Thomas Nelson, 2015)
The Complete 101 Collection includes material that in true Maxwell style helps readers reach their potential at any stage in their career. It can be thought of as a crash course in leadership, a practical tool to sharpen the core fundamentals every professional needs
Include Notes
Keywords: Leadership -- Management -- Success in business